2018
DOI: 10.1002/ejoc.201800279
|View full text |Cite
|
Sign up to set email alerts
|

Lipid A Structure and Immunoinhibitory Effect of the Marine Bacterium Cobetia pacifica KMM 3879T

Abstract: The structural elucidation of lipopolysaccharides (LPSs) from Gram‐negative marine bacteria, along with the assessment of their immunological properties, is a fascinating and active research field. Such studies can aid understanding of adaptation phenomena that occur in the marine environment, but they can also open up new perspectives on the design and development of new immunoregulatory drugs. In this paper, we report the structural characterization of the lipid A component of the LPS isolated from the marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Even more fascinating has been the observation of the potent inhibitory activity shown by both Echinicola LPS towards the proinflammatory response induced by the S. thypimurium LPS on HEK-Blue TM hTLR4 cells. This characteristic has been previously described for some other marine bacteria such as Halobacteroides lacunaris [11], Cobetia pacifica [10], as well as for the thermophilic bacterium Thermomonas hydrothermalis [35]. In this context, the present study further encourages the investigation of marine LPS as a never-ending source of natural molecules that can be potentially used to develop immunomodulatory compounds exploitable as therapeutics for inflammation-related pathologies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Even more fascinating has been the observation of the potent inhibitory activity shown by both Echinicola LPS towards the proinflammatory response induced by the S. thypimurium LPS on HEK-Blue TM hTLR4 cells. This characteristic has been previously described for some other marine bacteria such as Halobacteroides lacunaris [11], Cobetia pacifica [10], as well as for the thermophilic bacterium Thermomonas hydrothermalis [35]. In this context, the present study further encourages the investigation of marine LPS as a never-ending source of natural molecules that can be potentially used to develop immunomodulatory compounds exploitable as therapeutics for inflammation-related pathologies.…”
Section: Discussionsupporting
confidence: 81%
“…In this frame, LPS expressing unusual structural features are considered as potential inhibitors of the TLR4-mediated signaling. Manifold studies have revealed peculiar and uncommon LPS chemical structures from marine bacteria, which were reflected in an interesting immunological behavior that comprises a very weak immunostimulant activity or even antagonistic properties [3,[10][11][12]. Altogether, the structural elucidation of the lipid A from marine bacteria is certainly a fundamental starting point for the comprehension of the molecular details at the basis of adaptation processes, but it is also extremely important in the perspective of the realization of new generation immune-therapeutics inspired by a natural source.…”
Section: Introductionmentioning
confidence: 99%
“…HEX 311 lipid A (Scheme ) is mainly composed of tetra‐ and triacylated species, that is, a highly hypoacylated species, which might be poorly recognized by the sponge immune system. Moreover, if hexaacylated forms occur, these present a 3+3 distribution of the acyl chains, which are also typically correlated to a weak immunopotential . Therefore, the expression of lipid A with structural features leading to weak immunoactivity might be a key requirement to establish the successful symbiosis between the microbe and sponge.…”
Section: Resultsmentioning
confidence: 99%
“…However, virtually all knowledge of microbial detection has been derived from studies of bacteria that overlap ecologically with mammals, either in the same habitat or within mammalian hosts (10). With few exceptions (11)(12)(13), these studies focused on bacteria that inhabit terrestrial or shallow-depth aquatic environments (14), where mammals abound (15). But what of the bacteria that occupy different ecological niches?…”
Section: Introductionmentioning
confidence: 99%